Bracelets of Pride and Guilt? An Experimental Test of Self-Signaling in Charitable Giving - Joël J. van der Weele; Ferdinand von Siemens (Center for Economic Studies and ifo Institute (CESifo), 2014)
Self-signaling theory argues that individuals partly behave prosocially to create or uphold a favorable self-image. To study self-signaling theory, we investigate whether increasing self-image concerns affects charitable giving. In our experiment subjects divide 20 euros between themselves and a charity. Some randomly determined participants are induced to wear a bracelet for the two weeks following their donation decision. This bracelet serves as a private reminder of the experiment, thus making the donation more important for future self-image. If self-signaling plays a role, participants having to wear the bracelet should donate more. We do not find that wearing a bracelet has any effect on donation behavior. This holds although subjects having to wear the bracelet report that at the moment of making the donation, they expect to more often remember the experiment in the following two weeks.
Keywords: C91; C72; D83; 330; self-signaling; dictator games; charitable giving